A Quasi-experimental Study to Assess the Effectiveness of Nurse Empowerment Educational Program on Patient Safety Culture among the Staff Nurses of Selected Hospital in Kochi - David, Elizabeth; Solomon, Smriti G. (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of this study is to evaluate the effectiveness of nurse empowerment educational program on patient safety culture (SC) among the nurses of a selected hospital in Kochi. Method: The researcher adopted the quantitative evaluatory research approach and quasi-experimental research design. The sample size was 500 nurses from selected hospitals in Kochi who participated in the Nurse Empowerment Educational Program. In this study probability, purposive sampling technique was used. Result: In the pre-interventional patient SC (PSC) experimental group, 98 (39.2%) believe that PSC is average and 15 (6%) say excellent. In the control group, 101 (40.4%) answered that PSC is mediocre and 10 (4%) said good. In the post-interventional PSC experimental group, 110 (44%) reported an average culture and 14 (5.6%) reported a poor culture. In the control group, 104 (41.6%) thought that PSC is mediocre and 12 (4.8%) is good. In the experimental group, the nurse empowerment educational program significantly enhanced PSC among staff nurses (P < 0.05). This study found that the nurse empowerment program did not significantly enhance PSC among staff nurses in the control group (P < 0.05). Conclusion: The conclusions of the research corroborate the notion that staff nurses’ views regarding PSC are improved by the nurse empowerment educational program. The staff nurse’s patient safety score has increased.